The Role in Road Traffic Accident and Anxiety as Moderators Attention Biases in Modified Emotional Stroop Test - Ścigała, Dawid Konrad; Zdankiewicz-Ścigała, Elżbieta (Frontiers in Psychology, 2019)
Introduction: According to the WHO, road accidents will be the most common cause of premature death by 2020. According to research, one in every five victims of accidents suffers from ASD and one in every four suffers from psychological problems up to one year after the event, including PTSD. It was assumed that one of the mechanisms responsible for maintaining excessive arousal or anxiety is a dysfunction in cognitive processes occurring under the guise of selective attention disorders or a deficit in executive control. Materials and Methods: The research encompassed 157 individuals (a group of victims and perpetrators N=90; M=34.1, SD=10.77; control group N=67; M=34.20, SD=11.16). The participants, tested after road traffic accidents, were patients of Traumatology and Orthopaedic wards in Warsaw who had been involved in a road traffic accident up to a month prior to the research. The state of their physical injuries and administered drugs were monitored so that this did not interfere with the tests the participants undertook on computer. The participants from both groups completed the STAI questionnaire on anxiety as well as a modified computerised Emotional Stroop Test. This new version of the test enables a study of the process of the depth of coding of the stimuli associated with trauma. Results: The hypotheses were tested with the use of a series of correlation analyses, regression analyses with a stepwise method of entering predictors into the model, and mediation analyses. Differences were observed in the declarative level of anxiety as a state and the size of the interference effect depending on the person’s status in the accident. It was discovered that in the group of perpetrators, the longer the interference effect, the lower the declared level of anxiety as a state and they were significantly worse at remembering the stimuli associated with trauma. Conclusions: Anxiety symptoms in victims and perpetrators of road traffic accidents measured by self-report questionnaires are consistent only among victims. In the case of perpetrators, an accurate measure of disorders is a study with the use of methods enabling the tracking of the functioning of unconscious processes.